Marriage Under Age According to Indonesian Civil Law - Dewi, Aliya Sandra; Fitriana, Dian (PT FORMOSA CENDEKIA GLOBAL, 2024)
Early marriage is rampant in society. The lack of understanding and knowledge about this is the reason the author wants to raise and provide explanations to the community. Quoting from Indonesian Law Number 1 of 1974 concerning Marriage, which is contained in article 7 paragraph 1, it is stated that marriage is permitted if the prospective groom has reached the age of 19 (nineteen) years and the prospective bride has reached the age of 16 (sixteen) years. Amendments to the Law have been outlined in Law of the Republic of Indonesia Number 16 of 2019. The provision of the ideal age limit for marriage is stated in Article 7, which confirms that marriage is only permitted if the man and woman have reached the age of 19 (nineteen) years. Early marriage is problematic, both from the perspective of the Compilation of Islamic Law and the Marriage Law. Regarding the age limit of marriage, in Marriage Law Number 1 of 1974 which was later revised and became Marriage Law Number 16 of 2019. Based on this, the author will discuss the Sociological Impact for underage people who marry prematurely and the Legal Consequences of Underage Marriage According to Civil Law in Indonesia.